Gastric Disease Diagnosis Expert System With Bayes Method: Gastric Disease Diagnosis Expert System With Bayes Method - Nopriansya Nopriansya; Bosker Sinaga (Jurnal Mantik, 2019)
Helped develop information technology in line with the development of human civilization. In the health field, also developed a technology that is able to process and think like humans ie Artificial Intelligence technology. Artificial intelligence is divided into several areas of science, one of which is the expert system. expert systems can help people in gaining the desired information, khususnta information about diseases of the stomach. The stomach is an important organ in the body because it is one of the organs of digestion of food and beverages consumed by humans. To help people in making the diagnosis of diseases of the stomach, it would require an expert system that can diagnose diseases of the stomach in order to determine the type of the illness, symptoms dialamin and how treatment solutions. In this study, researchers made a gastric disease diagnosis expert system using Bayes methods. The data used is the type of disease, symptoms, and treatment solutions. This system will produce the output of information type of disease diagnosis and treatment of the disease.